Decompression sickness in coastal communities in Indonesia: A review - Yulia Puspita Sari; Nursafitri Anhufi (Journal of Epidemiology and Health Science, 2025)
Background: Decompression Sickness (DCS) is a prevalent health issue among coastal communities that rely heavily on diving activities, particularly traditional fishermen. Key risk factors associated with DCS include excessive diving depth, prolonged duration of dives, and frequent diving without adequate recovery time. Objective: This study aims to review existing literature on decompression sickness in coastal communities to identify its risk factors, associated health impacts, and effective prevention strategies. Methods: A literature review was conducted by analyzing 20 relevant articles that examine the incidence of DCS, contributing risk factors, and available treatment and prevention approaches. Results: The review findings indicate that diving to depths greater than 30 meters, remaining underwater for over 60 minutes, and rapid ascent to the surface are primary contributors to the occurrence of DCS. Educational programs on diving safety and the proper use of breathing apparatus have proven effective in reducing the risk of DCS among divers. Conclusion: To mitigate the incidence of decompression sickness in coastal communities, it is essential to implement comprehensive diving safety protocols, provide regular education and training for divers, and improve access to appropriate healthcare services. Keywords: Decompression Sickness, Coastal Communities, Risk Factors, Diving Safety, Health Education, Indonesia